Strategi Pengendalian Pencemaran Sungai Batang Lubuh di Kecamatan Rambah Kabupaten Rokan Hulu - Lydia Anna Oliza; Rifardi Rifardi; Zulkifli Zulkifli (EcoNews, 2021)
Batang Lubuh River is a river which is located in Rokan Hulu Regency. With approximately 151.9 Km (94.4 miles) in length, the river divides the capital of Rokan Hulu Regency Pasir Pengaraian into two parts. Because of the strategic location of the river, which is situated in the downtown, the government utilizes it as a waterfront city that attracts tourists with the local cuisines. The water from the Batang Lubuh River is the main raw material for clean water treatment which is managed by the government of Rokan Hulu Regency and distributed to Rambah sub-district. The purposes of this research were: to find out the water quality of the Batang Lubuh River; to determine the pollutant load of the Batang Lubuh River, which comes from its watercourses, namely, Menaming, Pawan, and Kaiti; to find out the load capacity of the Batang Lubuh River. The results of this research showed that the pollution index of the Batang Lubuh River is 2.38 which means that the river is lightly polluted. The pollution load that flow into the Batang Lubuh River for TSS, BOD5, total coliform, and oil and grease are 0,1350 mg/second; 0,0461 mg/second; 11,601 MPN/second and 0,0291 mg/second respectively, whereas the load capacity for TSS, BOD5, total coliform, and oil and grease in the Batang Lubuh River are 0,0412 mg/second; 0,0353 mg/second; 633,0638 MPN/second and 0,0743 mg/second respectively. Based on the findings, it can be stated that the Batang Lubuh River is not capable of purifying itself from the pollutant load such as TSS, BOD5, and oil and grease because the amount of pollutant load found in the river is bigger than the load capacity. However, the amount of total coliform found in the Batang Lubuh River is bigger than the pollutant load which means that the river still has the capability to recover itself from the pollutant load that flow into it. Based on the results of the model analysis using analytical hierarchy process (AHP), the alternatives found are as follows: 0.313 for supervision and monitoring, 0.288 for counseling/socialization, 0.203 for stakeholder coordination and 0.195 for law enforcement with the inconsistency value of 0.03.